Diverse, Cryptic, and Undescribed: Club and Coral Fungi in a Temperate Australian Forest - Vanessa J. McPherson; Michael R. Gillings; Timothy M. Ghaly (Journal of Fungi)
Fungi are the most poorly described kingdom of Eukarya. Fundamental questions about their species diversity, their distributions, and their biotic interactions remain largely unanswered, despite fungi playing important roles in the ecology and biogeochemistry of terrestrial ecosystems. To assess some of these data gaps, we intensively surveyed club and coral fungi in a temperate Australian forest in the Upper Lane Cove Valley, Sydney, Australia, over a period of two years. Specimens identified as Clavulinopsis, Ramaria, or Ramariopsis based on morphology were then assigned to operational taxonomic units (OTUs) using the criterion of 97% identity across the entire rDNA internal transcribed spacer (ITS) region. Based on this criterion and ITS-based phylogenies, we identified 80 OTUs in these genera of club and coral fungi within the survey area. Of these OTUs, only 11.25% could be assigned a species name based on BLASTn matches to full-length ITS sequences, suggesting that almost 90% of OTUs were novel taxa, or are yet to be represented in DNA databases. Specimens that were morphologically similar to well-known Northern Hemisphere species were shown to be distinct upon DNA sequencing. Accumulation curves suggest that our surveys only recovered about half of the species in the target genera, and seven times the effort would be required to sample to exhaustion. In summary, even in a small area of less than 100 km2, there is evidence for multiple undescribed, cryptic, and undiscovered species. This highlights the fundamental work that remains to be completed in fungal taxonomy and biology.